Integrating Environmental Accounting, Life Cycle and Ecosystem Services Assessment - Viglia, Silvio; Nienartowicz, Andrzej; Kunz, Mieczysław; Franzese, Pier Paolo (Journal of Environmental Accounting and Management, 2026)
Environmental protection is often considered as competing with human activities and economic development. On the contrary, more innovative guidelines recommend nature conservation to be achieved without banning human activities but, instead, developing appropriate management practices aimed at joint economic, social, and environmental sustainability. The suitability of such management schemes should be evaluated through integrated assessment frameworks overcoming mono-dimensional metrics and criteria. In this study, we integrated different environmental accounting methods with life cycle and ecosystem services assessment to investigate the interplay of human activities and nature conservation in the Bory Tucholskie National Park (Poland). Indicators of environmental costs and impacts due to the exploitation of forest ecosystem services in the study area were calculated. In addition, the economic and ecological value of the main forest ecosystem services was assessed to explore the benefits gained in preserving stocks of natural capital while exploiting flows of eco- system services.